The Influence of Financial Literacy, Locus of Control, Government Support and Access to Capital on Financial Behavior in Business Sustainability in MSMEs in Sambas Regency - Dahlima, Dahlima; Hariyanto, Dedi; Safitri, Heni (Journal of Asian Multicultural Research for Economy and Management Study, 2024)
This study aims to analyze the influence of financial literacy, locus of control, government support, and access to capital on the financial behavior of Micro, Small, and Medium Enterprises (MSMEs) in Sambas Regency, Indonesia. The objective is to understand how these factors contribute to the sustainability and growth of MSMEs in the region. A quantitative research approach was employed, involving a survey of 100 MSME owners in Sambas Regency. Data were collected through structured questionnaires and analyzed using multiple regression analysis to determine the relationship between financial literacy, locus of control, government support, access to capital, and financial behavior. The results indicate that financial literacy, locus of control, and access to capital have a significant positive impact on the financial behavior of MSME owners. Government support also plays a crucial role in enhancing financial behavior, although its impact is comparatively moderate. Collectively, these factors are essential for the financial sustainability and success of MSMEs in Sambas Regency.